Revitalisasi Idealitas Pengelolaan Keuangan Pendidikan: Studi Masa Khalifah Umar bin Abdul Aziz - Muh Nur Islam Nurdin; Erni Munastiwi (Lembaga Sosial Rumah Indonesia, 2023)
Financial management in education holds a central position in building an effective and sustainable education system. However, during the era of Umar bin Abdul Aziz, it did not receive adequate historical attention. This research aims to evaluate the financial management of education during that period through a descriptive literature study. The results indicate that financial management of education at that time encompassed financial planning, fair salary distribution, infrastructure development, and administrative evaluation such as fund recording. Umar bin Abdul Aziz also promoted values of integrity in governance. A progressive and transformative educational leader is needed for dynamic education policies and optimal financial management. In conclusion, the role of key leaders is crucial in creating a robust and sustainable education system.